A linguagem do humor e do desejo em Dona Flor e seus Dois Maridos - Alba Valéria Tinoco Alves Silva (Entrepalavras: Revista de Linguística do Departamento de Letras Vernáculas da Universidade Federal do Ceará, 2016)
The aim of this article is to propose a reading of the novel Dona Flor e seus dois maridos by Jorge Amado, guided by two of its constituent elements: the construction of the comic characters from the point of view of their obsessive traits and the representation of desire based on the love triangle played by Dona Flor, the teacher of culinary, and her two husbands, Waldomiro dos Santos Guimarães, also called Vadinho, and Teodoro Madureira, the pharmacist. To account for these aspects, the theoretical framework of this paper follows two different strands. In terms of erotic language, the main reference is the work of Affonso Romano de Sant’Anna, O canibalismo amoroso, 1984. On the side of the construction of humor, the main references are Vilma Áreas, Iniciação à comédia, 1999; Vladimir Propp, Comicidade e riso, 1992, and Cleise Mendes, A gargalhada de Ulisses, 2008.The aim of this article is to propose a reading of the novel Dona Flor e seus dois maridos by Jorge Amado, guided by two of its constituent elements: the construction of the comic characters from the point of view of their obsessive traits and the representation of desire based on the love triangle played by Dona Flor, the teacher of culinary, and her two husbands, Waldomiro dos Santos Guimarães, also called Vadinho, and Teodoro Madureira, the pharmacist. To account for these aspects, the theoretical framework of this paper follows two different strands. In terms of erotic language, the main reference is the work of Affonso Romano de Sant’Anna, O canibalismo amoroso,1984. On the side of the construction of humor, the main references are  Vilma Áreas, Iniciação à comédia, 1999; Vladimir Propp, Comicidade e riso, 1992, and Cleise Mendes, A gargalhada de Ulisses, 2008.